Current overview and treatment of mantle cell lymphoma - Schieber, Michael (F1000Res, 2018)
Mantle cell lymphoma (MCL) is a B-cell non-Hodgkin lymphoma with historically poor long-term survival compared with other B-cell malignancies. Treatment strategies for this disease are variable and dependent on symptoms and patient fitness. Despite recent advances, MCL remains incurable and patients with high-risk disease have particularly poor outcomes. This review focuses on recent developments that enhance our understanding of the biology of MCL and new treatment approaches that have led to substantial improvements in clinical outcomes. We will outline induction immuno-chemotherapy and maintenance strategies in transplant-eligible patients. In addition, effective strategies for patients unfit for intensive induction will be discussed, with a particular focus on novel molecular therapies with activity in MCL. Lastly, a number of ongoing clinical trials will be presented; the data from these trials are anticipated to redefine standards of care in the near future.